Strategies for Developing Digital Competencies in Human Resources to Improve Service Quality - Vettyca Diana Saputri (Utami Publisher, 2026)
This study aims to analyze the digital competency development strategy of human resources (HR) in improving service quality at the BRI Branch Office (KC) in Bengkulu City. In an era of rapid digital transformation, the ability of HR to master digital technology has become a key factor in the success of banking services. This study uses a descriptive qualitative approach with the Miles and Huberman data analysis method, which includes three stages: data reduction, data display, and conclusion drawing/verification. Data collection was carried out through in-depth interviews, observation, and documentation studies. Research informants were selected using purposive sampling, consisting of Branch Manager, HR Manager, and employees of KC BRI Bengkulu City. The results show that KC BRI Bengkulu City implements several digital competency development strategies including: (1) regular digital technology-based training, (2) digital mentoring and coaching programs, (3) digital competency certification, and (4) performance evaluation based on digital indicators. These strategies proved to contribute significantly to improving service quality as indicated by increased customer satisfaction and service efficiency.